2013
DOI: 10.1093/jac/dkt044
|View full text |Cite
|
Sign up to set email alerts
|

Frequent emergence of porin-deficient subpopulations with reduced carbapenem susceptibility in ESBL-producing Escherichia coli during exposure to ertapenem in an in vitro pharmacokinetic model

Abstract: The combination of ESBL production and porin loss in E. coli can result in reduced susceptibility to ertapenem. Porin-deficient subpopulations frequently emerged in ESBL-producing E. coli during exposure to ertapenem at concentrations simulating human pharmacokinetics. Inappropriate use of ertapenem should be avoided to minimize the risk of selection of ESBL-producing bacteria with reduced susceptibility to carbapenems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 21 publications
6
59
0
1
Order By: Relevance
“…Our study showed that the Gly-63-Val substitution in OmpR renders the expression of ompC and ompF inactive. These results are in agreement with the in vitro studies of Tängdén et al and Adler et al, which demonstrated that a single-step EnvZ-or OmpR-inactivating mutation was enough to significantly increase the MIC for ertapenem due to a subsequent reduction of OmpC and/or OmpF of up to 90% (23,24). Our report provides further evidence for the clinical relevance of OmpR change in the emergence of ertapenem resistance among E. coli clinical isolates.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed that the Gly-63-Val substitution in OmpR renders the expression of ompC and ompF inactive. These results are in agreement with the in vitro studies of Tängdén et al and Adler et al, which demonstrated that a single-step EnvZ-or OmpR-inactivating mutation was enough to significantly increase the MIC for ertapenem due to a subsequent reduction of OmpC and/or OmpF of up to 90% (23,24). Our report provides further evidence for the clinical relevance of OmpR change in the emergence of ertapenem resistance among E. coli clinical isolates.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the MIC of E. coli ErtR for imipenem remained unchanged. This discrepancy, which was also evidenced in the study of Tängdén et al (23), could be attributable to the intrinsic hydrolysis spectrum of CTX-M ␤-lactamases. The full restoration of the MIC value of E. coli ErtR for meropenem by clavulanic acid supported this hypothesis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Mutants resistant to these antibiotics were obtained for all the strains with the exception of the ESC-susceptible strains S250 and CFT073, for which no increase in ETP MICs was noted after 5 months of subculture. These results were in agreement with those of Tangden and Girlich, who also observed that carbapenem resistance in E. coli was selected only among ESBL-producing strains (27,47).…”
Section: Figsupporting
confidence: 93%
“…Meropenem alone resulted in increased killing relative to fosfomycin, but it did not result in extinction. We did not observe any meropenem-resistant mutants, although it is possible that a low level of mutants was present but not detectable (30). The combination of fosfomycin and meropenem resulted in a Ͼ10-log 10 CFU/ml kill and sterilization of the bacterial inoculum after 48 h of treatment.…”
Section: Discussionmentioning
confidence: 67%